(untitled) (International Journal of Engineering and Computer Science, 2017)
Reversible logic is one of the most essential issues at present time due to its power reduction capability in circuit designing. It finds application in various fields including quantum computing , optical computing , nano technology , computer graphic , cryptography . Dissipation of a significant amount of energy is achieved in the conventional digital circuits because bits of information are erased during the logic operations. Thus, if logic gates are designed in such a way that the information bits are not destroyed, then it is possible to reduce the power consumption dramatically. The information bits are not lost in case of a reversible computation. This has led to the development of reversible gates. The reversible circuits do not lose information and can generate unique outputs from the specified inputs. The main purposes of designing reversible logic are to decrease quantum cost and the number of garbage outputs. This paper represents the realization of different MULTIPLEXERS and a MULTI LOGIC FUNCTION GENERATOR circuit for generating multiple logical functions simultaneously using COG gates. And a CONTROLLED MULTI LOGIC FUNCTION GENERATOR circuit for generating any specified output in a controlled way. This paper also proposes the design of ALU which have better performance in terms of quantum cost. The proposed work leads to an improvement of 20% and 17% in terms of gate count and quantum cost. The simulation and verification of these are done in XILINX software.